2011
DOI: 10.1016/j.neuro.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Mn and Pb by rats during and after pregnancy alters iron metabolism and behavior in offspring

Abstract: Manganese (Mn) and lead (Pb) exposures during developmental period can impair development by direct neurotoxicity or through interaction with iron metabolism. Therefore, we examined the effects of maternal ingestion of Mn or Pb in drinking water during gestation and lactation on iron metabolism as well as behavior in their offspring. Pregnant dams were given distilled water, 4.79 mg/ml Mn, or 2.84 mg/ml Pb in drinking water during gestation and lactation. Pups were studied at time of weaning for 59Fe absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 52 publications
8
41
0
2
Order By: Relevance
“…Hence, the prolonged time spent in the open arms in Mn-instilled mice indicates that olfactory Mn exposure decreases anxiety and/or increases impulsivity, likely by deficits in disinhibition control. These results are in line with our previous findings that Mn-exposed rat pups reduce anxiety-related behavior (Molina et al, 2011). We note that our results are disparate from those by Kern et al (Kern et al, 2010), who reported no behavioral changes upon Mn exposure by the EPM test, likely due to different exposure protocols and routes of administration (i.e., oral administration during the preweaning stage (Kern et al, 2010) vs. intranasal instillation to mice after weaning in the present study).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the prolonged time spent in the open arms in Mn-instilled mice indicates that olfactory Mn exposure decreases anxiety and/or increases impulsivity, likely by deficits in disinhibition control. These results are in line with our previous findings that Mn-exposed rat pups reduce anxiety-related behavior (Molina et al, 2011). We note that our results are disparate from those by Kern et al (Kern et al, 2010), who reported no behavioral changes upon Mn exposure by the EPM test, likely due to different exposure protocols and routes of administration (i.e., oral administration during the preweaning stage (Kern et al, 2010) vs. intranasal instillation to mice after weaning in the present study).…”
Section: Discussionsupporting
confidence: 93%
“…Lead has adverse effects to mainly renal, hematopoietic and neurologic systems. The most susceptible populations to the adverse neurodevelopmental effects of lead are children, particularly infants in the neonatal period and fetus since neurodevelopment begins in this period and the blood-brain barrier is still immature (Goyer, 1990;Goyer, 1997;Molina et al, 2011). Moreover, exposure levels that do not harm the mother can be fetotoxic because of the differences between the many biochemical pathways of the adult and the fetus (Baghurst et al, 1991;Al-Saleh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental models, it was demonstrated that umbilical cord blood flow rate affected the transfer of lead linearly (Goyer, 1990). Furthermore, iron deficiency or dietary iron consumption of the mother can also alter lead uptake (Molina et al, 2011). Hence, genes related to iron metabolism could modify lead absorption and pregnant women with genetic variants affecting iron metabolism could have children at increased risk of exposure to lead.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, once within the cells, a particular metal may occupy abundant binding sites [27] on metalloproteins or target molecules, in turn, modifying the compartmentalization of other metals, thus leading to aberrant binding and toxicity [26]. A given metal may induce overexpression of transporters and/or binding proteins that alter the uptake of other metals [27, 28]. These events may modify the uptake and/or retention of metals in cells, affecting their toxicokinetics profile and toxicity [1, 29].…”
Section: Introductionmentioning
confidence: 99%